(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The socio-economic relations of the state and business have a dialectical connection, the force of interaction, which originates from the essence of who and which forces organize and control the production capacity of the society and the process of extended reproduction. If business, for example, accepts the capitalist development model and achieves the acceptance of business values and goals by society and the state, the country’s development path will fall into a mold like a railway track with a “state capture” scenario. As long as the state apparatus (managers) is (are) able to impose its will on the business based on the values of the society, it means that the business capture model has emerged. But for the development of society, the most fundamental and important issue is not who has influenced whom, but what values, what goals (intended for the medium and long term) form the content and essence of the management model. It is these values that define the country’s development path (track) like a railway track, and it is precisely because of this that it is impossible to get out of it easily. The problem is that the content of values is not determined by who manages or controls what (business or state apparatus). The content of values is determined by the people’s ability to integrate their will into the consciousness and practice of the above two forces.